Midtrimester spontaneous torsion of unruptured gravid rudimentary horn: Presurgical diagnosis on magnetic resonance imaging. Issue 9 (27th May 2015) - Singh, Pragya; Gupta, Rohini; Das, Banashree; Bajaj, Sunil Kumar; Misra, Ritu
Abstract Unicornuate uterus with rudimentary horn occurs due to failure of complete development and partial fusion of one of the Müllerian ducts. Pregnancy in a non‐communicating rudimentary horn is extremely rare, with a reported incidence of 1 in 76 000–150 000 pregnancies, and usually terminates in rupture during the first or second trimester. Clinical diagnosis of rudimentary horn pregnancy in a woman with history of normal vaginal delivery in prior gestations is difficult. The role of sonography, and more recently, magnetic resonance imaging, in the presurgical diagnosis of rudimentary horn pregnancy is established. We present a case of magnetic resonance imaging diagnosis of 20‐week pregnancy in the unruptured non‐communicating rudimentary horn in a patient with previous history of two full‐term normal vaginal deliveries. The novelty of the case lies in the fact that there was associated torsion of the gravid rudimentary horn and ipsilateral ovary, which has not been reported previously.